Hadith #1599 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
The people doubted whether the Prophet (ﷺ) was observing the fast on the Day of `Arafat, so I sent something for him to drink and he drank it.
Grade: Sahih

Hadith #1602 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
On the day of `Arafat, some people who were with me, differed about the fasting of the Prophet (ﷺ) (p.b.u.h) some said that he was fasting while others said that he was not fasting. So I sent a bowl full of milk to him while he was riding his camel, and he drank that milk.
Grade: Sahih

Hadith #1917 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
“While the people were with me on the day of `Arafat they differed as to whether the Prophet (ﷺ) was fasting or not; some said that he was fasting while others said that he was not fasting. So, I sent to him a bowl full of milk while he was riding over his camel and he drank it.”
Grade: Sahih

Hadith #2579 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
That when the Ansar drew lots as to which of the emigrants should dwell with which of the Ansar, the name of `Uthman bin Mazun came out (to be in their lot). Um Al-Ala further said, “Uthman stayed with us, and we nursed him when he got sick, but he died. We shrouded him in his clothes, and Allah’s Apostle came to our house and I said, (addressing the dead `Uthman), ‘O Abu As-Sa’ib! May Allah be merciful to you. I testify that Allah has blessed you.’ The Prophet (ﷺ) said to me, “How
Grade: Sahih

Hadith #3039 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
the daughter of Abu Talib: I went to Allah’s Messenger (ﷺ) on the day of the conquest of Mecca and found him taking a bath, and his daughter Fatima was screening him. I greeted him and he asked, “Who is that?” I said, “I, Um Hani bint Abi Talib.” He said, “Welcome, O Um Hani.” When he had finished his bath, he stood up and offered eight rak`at while dressed in one garment. I said, “O Allah’s Messenger (ﷺ)! My brother `Ali has declared that he will kill a man to whom I have
Grade: Sahih

Hadith #3766 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
An Ansari woman who gave the pledge of allegiance to the Prophet (ﷺ) that the Ansar drew lots concerning the dwelling of the Emigrants. `Uthman bin Maz’un was decided to dwell with them (i.e. Um Al-`Ala’s family), `Uthman fell ill and I nursed him till he died, and we covered him with his clothes. Then the Prophet (ﷺ) came to us and I (addressing the dead body) said, “O Abu As-Sa’ib, may Allah’s Mercy be on you! I bear witness that Allah has honored you.” On that the Prophet (ﷺ
Grade: Sahih

Hadith #4235 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
I heard the Prophet (ﷺ) reciting Surat-al-Mursalat `Urfan (77) in the Maghrib prayer, and after that prayer he did not lead us in any prayer till he died.
Grade: Sahih

Hadith #5391 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
The people doubted whether Allah’s Messenger (ﷺ) was fasting or the Day of `Arafat or not. So I sent a cup containing milk to him and he drank it.
Grade: Sahih

Hadith #5405 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
(daughter of Al-Harith) that she sent a bowl of milk to the Prophet (ﷺ) while he was standing (at `Arafat) in the afternoon of the Day of `Arafat. He took it in his hands and drank it. Narrated Abu Nadr: The Prophet was on the back of his camel.
Grade: Sahih

Hadith #5423 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
that the people were in doubt whether the Prophet (ﷺ) was fasting on the Day of `Arafat or not, so a (wooden) drinking vessel full of milk was sent to him, and he drank it.
Grade: Sahih

Hadith #5498 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
that she took to Allah’s Messenger (ﷺ) one of her sons whose palate and tonsils she had pressed to treat a throat trouble. The Prophet (ﷺ) said, “Be afraid of Allah! Why do you pain your children by having their tonsils pressed like that? Use the Ud Al-Hindi (a certain Indian incense) for it cures seven diseases, one of which is pleurisy.”
Grade: Sahih

Hadith #5925 - Sahih al-Bukhari - Um Al-Fadl (Sahih al-Bukhari)
(the daughter of Abu Talib) I visited Allah’s Messenger (ﷺ) in the year of the Conquest of Mecca and found him taking a bath, and his daughter, Fatima was screening him. When I greeted him, he said, “Who is it?” I replied, “I am Um Hani, the daughter of Abu Talib.” He said, “Welcome, O Um Hani ! ” When the Prophet (ﷺ) had finished his bath, he stood up and offered eight rak`at of prayer while he was wrapped in a single garment. When he had finished his prayer, I said, “O Alla
Grade: Sahih